Workplace Ostracism as a Determinant of Mental Health among Teachers - Nishant Kumar; Dr. Sandeep Kumar (International Journal of Indian Psychȯlogy, 2025)
Workplace ostracism the experience of being ignored, excluded, or rejected by colleagues and superiors is increasingly recognized as a critical yet underexplored factor affecting employees’ mental health. This study examines the impact of workplace ostracism on the mental health of teachers, a group particularly vulnerable due to the interpersonal and collaborative nature of their profession. The study’s sample comprised 100 Teachers from the Vaishali District. Data were collected during 2025 using the Workplace ostracism scale by Ferris to assess workplace ostracism and the mental health scale by Keyes to measure mental health. The data were then analyzed using descriptive statistics, Pearson’s product-moment correlation, and simple linear regression (SLR) through SPSS. The findings revealed a significant negative correlation between workplace ostracism and mental health and its dimensions, suggesting potential strategies for addressing it in organizational settings.